Neural aspects of brand love - Cayolla, Ricardo (2016)
Brand love has been identified as a key driver for behavioral outcomes such as brand loyalty, positive WOM or price premium. While we know a great deal about the psychological aspects of brand love, we know very little about the neural ones. The purpose of this paper is to explore this. We used a 3 (positive, negative, neutral video stimuli) x 2 (strong vs. weak brand) experimental design. To assess the neural aspects, 53 participants underwent fMRI scans while watching short video clips and rated them on a 7-point bipolar scale (-3 = very negative; +3 = very positive). Our results suggest a ‘negativity bias paradox’ in contradiction findings from psychology literature (based on attitudinal data) that negative events exert greater impact on consumer behavior than positive ones. We also find evidence for a ‘strong brand paradox’ with fans of the weaker brand showing greater neural activities than fans of the stronger brand which contradicts findings from consumer behavior research.